PENGARUH CURRENT RATIO (CR), NET PROFIT MARGIN (NPM), DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PT HM SAMPOERNA TBK PERIODE 2013-2022 - Gilang Bilal Nuriksa; Hengki Hermawan (Journal of Research and Publication Innovation, 2025)
This research aims to find out whether there is a significant influence between Current Ratio, Net Profit Margin, and Earning Per Share on Stock Prices. The method used in this research is a quantitative method in collecting Financial Report data from PT HM Sampoerna Tbk for the 2012-2022 period. Data analysis uses descriptive statistical analysis, classical assumption tests, simple linear regression analysis, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this research show that the Current Ratio has no significant effect on Stock Prices, Net Profit Margin has no significant effect on Stock Prices, and Earning Per Share shows that it has an influence on Stock Prices. The Effect of Current Ratio, Net Profit Margin, and Earning Per Share on Prices Shares in PT HM Sampoerna Tbk for the 2013-2022 period. Based on the results of the F test, the calculated F value > F table or (176.514 > 4.740) is obtained. This is also confirmed by the p value < Sig. 0.05 or (0.003<0.05)